Chronic Stress Alters Behavior in the Forced Swim Test and Underlying Neural Activity in Animals Exposed to Alcohol Prenatally: Sex- and Time-Dependent Effects - Lam, Vivian Y. Y.; Raineki, Charlis; Takeuchi, Lily E.; Ellis, Linda; Woodward, Todd S.; Weinberg, Joanne (Frontiers in Behavioral Neuroscience, 2018)
Dysregulation of the hypothalamic-pituitary-adrenal (HPA) stress response has been suggested to play a role in vulnerability to stress-related disorders, such as depression. Prenatal alcohol exposure (PAE) may result in HPA dysregulation, which in turn may predispose individuals to the effects of stress exposure throughout life, and increase their risk of developing depression compared to unexposed individuals. We examined the immediate and delayed effects of chronic unpredictable stress (CUS) in adulthood on behavior of PAE animals in the forced swim test (FST) and the neurocircuitry underlying behavioral, emotional, and stress regulation. Adult male and female offspring from PAE and control conditions were tested for 2 days in the FST, with testing initiated either 1 day (CUS-1; immediate) or 14 days (CUS-14; delayed) post-CUS. Following testing, c-fos mRNA expression of the medial prefrontal cortex (mPFC), amygdala, hippocampal formation, and the paraventricular nucleus of the hypothalamus was assessed. Our results indicate that PAE and CUS interact to differentially alter FST behaviors and neural activation of several brain areas in males and females, and effects may depend on whether testing is immediate or delayed post-CUS. PAE males showed decreased time immobile (Day 1 of FST) following immediate testing, while PAE females showed increased time immobile (Day 2 of FST) following delayed testing compared to their respective control counterparts. Moreover, in males, PAE decreased c-fos mRNA expression in the lateral and central nuclei of the amygdala in the non-CUS condition, and increased c-fos mRNA expression in the CA1 in the CUS-14 condition. By contrast in females, c-fos mRNA expression in the Cg1 was decreased in PAE animals (independent of CUS) and decreased in all mPFC subregions in CUS-14 animals (independent of prenatal treatment). Constrained principal component analysis, used to identify neural and behavioral networks, revealed that PAE altered the activation of these networks and modulated the effects of CUS on these networks in a sex- and time-dependent manner. This dysregulation of the neurocircuitry underlying behavioral, emotional and stress regulation, may ultimately contribute to an increased vulnerability to psychopathologies, such as depression, that are often observed following PAE.